Implementation of nutrition screening for older adults improves outcomes and is well-received by patients in Australian general practice settings - Hamirudin, Aliza Haslinda; Charlton, Karen; Walton, Karen; Bonney, Andrew; Albert, George; Hodgkins, Adam; Potter, Jan; Milosavljevic, Marianna; Ghosh, Abhijeet; Dalley, Andrew (Academy of Family Physicians of Malaysia, 2015)

(untitled)
Introduction: Nutrition screening for older adults is feasible to include in routine visits to their General Practitioners. Objectives: This study aimed to identify the perceptions of older patients related to their experiences when undergoing the nutrition screening process, and to evaluate outcomes post nutrition screening. Method: Patients aged ≥75 years (n=143) who had participated in an initial nutrition screening were invited for repeat screening between 6 months and one year following the first screening. Those who were malnourished and at risk at baseline were invited to participate in an individual interview at follow-up to identify their perceptions of the Mini Nutritional Assessment Short Form (MNA-SF) and the usefulness of a nutrition resource kit that had been provided. Interviews were audio recorded, transcribed verbatim, coded into topics and analysed thematically using NVivo software version 10. Statistical analyses were performed using SPSS, with significance set at p < 0.05. Results: Seventy-two patients (50.3%) underwent repeat screening. Nutritional status had improved in the group identified to be malnourished/at risk at baseline (p= 0.01), while no significant changes were detected for the wellnourished group (p=0.07). Referral to community services predicted malnutrition risk score at follow-up (p= 0.031). Interviews indicated that the MNA-SF process itself was wellreceived but that patients did not perceive themselves as being in need of nutrition support. Conclusion: Implementation of routine identification of malnutrition in older adults attending general practice can be achieved with the use of a rapid screening tool. Further deterioration in nutritional status may then be prevented by following appropriate nutrition care pathways, including referral to community services. The MNA-SF was not perceived by older patients as being harmful, or intrusive, however motivators for older patients to improve their nutritional status warrants further exploration.